2021
DOI: 10.1016/j.ajem.2020.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic manifestations of COVID-19

Abstract: Introduction Coronavirus disease of 2019 (COVID-19) is a lower respiratory tract infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This disease can impact the cardiovascular system and lead to abnormal electrocardiographic (ECG) findings. Emergency clinicians must be aware of the ECG manifestations of COVID-19. Objective This narrative review outlines the pathophysiology and electrocardiographic findings associated with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 84 publications
3
88
1
9
Order By: Relevance
“…Several previous reviews have described the manifestations of COVID‐19 patients on ECG abnormalities and the effect of medications such as chloroquine, hydroxychloroquine, and azithromycin on QTc prolongation and its association to poor outcomes. Other studies in patients who were not treated with the drugs mentioned above have found that ECG findings associated with mortality and morbidity limited to PR interval changes, axis changes, unspecific ST‐T abnormalities, and cardiac arrhythmias such as atrial fibrillation (AF), supraventricular tachycardia (SVT), ventricular tachycardia (VT), and ventricular fibrillation (VF) 20,21 . To the best of our knowledge, this is the first systematic review and meta‐analysis to describe the abnormality of each ECG parameter on admission and to evaluate its association with the outcomes of COVID‐19 patients and adds several new findings, where prolonged QRS findings, LBBB, and PACs and PVCs are associated with worse outcomes in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous reviews have described the manifestations of COVID‐19 patients on ECG abnormalities and the effect of medications such as chloroquine, hydroxychloroquine, and azithromycin on QTc prolongation and its association to poor outcomes. Other studies in patients who were not treated with the drugs mentioned above have found that ECG findings associated with mortality and morbidity limited to PR interval changes, axis changes, unspecific ST‐T abnormalities, and cardiac arrhythmias such as atrial fibrillation (AF), supraventricular tachycardia (SVT), ventricular tachycardia (VT), and ventricular fibrillation (VF) 20,21 . To the best of our knowledge, this is the first systematic review and meta‐analysis to describe the abnormality of each ECG parameter on admission and to evaluate its association with the outcomes of COVID‐19 patients and adds several new findings, where prolonged QRS findings, LBBB, and PACs and PVCs are associated with worse outcomes in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 93%
“…Regardless of whether COVID-19 exacerbates preexisting CVD or causes new structural/functional abnormalities 24 , early detection of such conditions may be valuable for patient management. Several symptoms of COVID-19, such as chest pain and marked dyspnea, overlap with those of acute CVD 25 , 26 , and observational data suggest that electrocardiographic abnormalities and elevated biomarkers of cardiac injury are also prevalent, especially in severely ill individuals 20 , 24 , 27 . This, along with the high cardiovascular risk profile of hospitalized individuals, as evidenced in our sample, may trigger requests for echo in a large majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the relevance of electrocardiography (ECG) in COVID-19 patients. In these studies, it was reported that many changes such as supraventricular tachycardia, malignant ventricular arrhythmia, bradycardia, atrioventricular block, ST segment, T wave and QRS complex abnormalities and QT prolongation can be observed in COVID-19 patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%